An Inventory of Ferns (Pteridophyta) in Plantation PTPN Nusantara 3 Rantau Prapat District Labuhanbatu - Jahot Tua Situmorang; Rosmidah Hasibuan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
PTPN Nusantara 3 is one of the Companies engaged in the field of Rubber plantations and Palm oil that has a wide 9.150,80 ha. Rubber plantation PTPN Nusantara 3 Rantau Prapat is one area that there are many ferns. Ferns (Pteridophyta) are most commonly found in the area of rubber Plantation PTPN Nusantara 3 Rantau Prapat District Labuhanbatu is a family Dryopteridaceaese lot of 6 species, namely Nephrolepisbiserrata, Nephrolepiscor difolia, Nephrolepi sexaltata, Nephrolepissp, Ploecnemia irregularis and Stenochlaenae palustris. Based on the results of research conducted by researchers on 03-May-11 May 2021 in the rubber Plantation PTPN Nusantara 3 Rantau Prapat District Labuhanbatu, researchers found 7 famili ferns (Pteridophyta), namely Aspleniaceae, Blechnaceae, Davalliaceae, Dryopteridaceae, Gleicheniaceae, Lycopodiaceae, Polypodiaceae, with 17 species of ferns (Pteridophyta). Abiotic factors that can affect the growth of the nail is different because according to his needs, namely air temperature 29C-32 C while the soil moisture that is up 7.9%-69% and the pH of the soil ranged from 8.00 8,90.